2002
DOI: 10.1002/art.10228
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of rheumatoid arthritis with methotrexate and hydroxychloroquine, methotrexate and sulfasalazine, or a combination of the three medications: Results of a two‐year, randomized, double‐blind, placebo‐controlled trial

Abstract: Objective. To compare the efficacy of combination therapy with methotrexate (MTX) and hydroxychloroquine (HCQ), MTX and sulfasalazine (SSZ), and MTX, HCQ, and SSZ in patients with rheumatoid arthritis (RA).Methods. RA patients (n ‫؍‬ 171) who had not previously been treated with combinations of the study medications were randomized to receive 1 of the 3 treatment combinations in this 2-year, double-blind, placebo-controlled protocol. HCQ was given at a dosage of 200 mg twice a day. The dosage of MTX was accele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
108
0
6

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 275 publications
(127 citation statements)
references
References 22 publications
10
108
0
6
Order By: Relevance
“…The superiority of combination therapy over single therapy in the FIN-RACo trial (4) has been confirmed by other studies with regard to the short-term clinical outcome of patients with early RA (3,5). These findings have resulted in increased optimism with regard to the ability of DMARD combinations to reduce structural joint damage as well, even over the long term.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…The superiority of combination therapy over single therapy in the FIN-RACo trial (4) has been confirmed by other studies with regard to the short-term clinical outcome of patients with early RA (3,5). These findings have resulted in increased optimism with regard to the ability of DMARD combinations to reduce structural joint damage as well, even over the long term.…”
Section: Discussionmentioning
confidence: 76%
“…Moreover, the ESR and serum CRP levels were low, even in RA patients who were not in remission (Figure 3). The median DAS28 scores in the combination and single groups were as follows: at baseline, 5 Figure 4). The time-weighted mean Ϯ SD DAS28 area under the curve from baseline up to 5 years was 2.70 Ϯ 1.07 in the combination group and 3.40 Ϯ 1.06 in the single group (P Ͻ 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another strategy of the rheumatologist for enhancing the efficacy of the combination of MTX plus SSZ is the addition of a third drug (e.g., hydroxychloroquine [13] or prednisone [14]) to the MTX-SSZ combination. Although the objective of this study was not to elucidate a mechanistic basis for the efficacy of the triple DMARD therapy, recent studies by our group (47) did indicate that CEM/SSZ cells displayed enhanced sensitivity to both chloroquine and dexamethasone.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, addition of a third component such as hydroxychloroquine (12,13) or prednisone (14) is usually required to significantly improve clinical efficacy. Furthermore, one notable adverse effect observed was a persistent increase in plasma homocysteine levels in patients with RA who were receiving the combination of MTX and SSZ, compared with those receiving single-drug therapy (15,16).…”
mentioning
confidence: 99%